Reported chemical sensitivities in a health survey of United Kingdon military personnel. Issue 3 (1st March 2002) - Reid, S; Hotopf, M; Hull, L; Ismail, K; Unwin, C; Wessely, S
Abstract : Objective: To report the prevalence of self reported chemical sensitivities in three cohorts of United Kingdom service personnel. Method: Cross sectional postal survey of three cohorts of United Kingdom military personnel comprising Gulf veterans (n=3531), those who had served in Bosnia (n=2050), and those serving during the Gulf war but not deployed there (Era cohort, n=2614). Results: Sensitivity to at least one everyday chemical was reported by a considerable proportion of all three cohorts, and particularly by veterans of the Gulf war (Era: 14%; Bosnia: 13%; Gulf: 28%). Conclusion: Reported chemical sensitivities were common in all three military cohorts. Our understanding of chemical sensitivities remains limited and objective evidence for a causal link between low level exposures to chemicals and reported symptoms is lacking. Given their frequency in the population, further work in this area is necessary.